Going off script: improvisational judgment in the Talmud - Barer, Deborah (Oxford University Press, 2026)
"Going Off Script traces the development of the Talmudic category of acting lifnim mi-shurat ha-din. It demonstrates how the Talmudic editors develop this category to respond to set of legal and textual problems in a set of inherited narrative traditions. The editors account for these challenges by arguing that the figures in these stories improvise, rather than sticking to established scripts for action. In so doing, the editors develop a new framework for analyzing behavior that mediates the rigidity of rabbinic rules and scripts, offering a way to actualize new moral possibilities. Improvisation also, however, comes with its own challenges. Even as the editors develop this category, they work to contain its destabilizing implications"-- Provided by publisher